2009
DOI: 10.1080/07399330902928873
|View full text |Cite
|
Sign up to set email alerts
|

Managing Motherhood: Strategies Used by New Mothers to Maintain Perceptions of Wellness

Abstract: The first year or so of motherhood can represent a transitional lifestyle change; however, experiences are not well understood from the mother's own perspective. In a series of interviews, nine mothers related their beliefs and ideas about strategies utilized to maintain a perceived sense of wellness. The mothers used three main strategies: (a) obtaining help, (b) having a plan, and (c) taking time-out. Discovery of a successful strategy lead to a mother feeling greater confidence in the efficacy of her select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 25 publications
3
13
0
9
Order By: Relevance
“…Physical activity is an everyday practice through which women may open up a space for "self-fashioning" and a chance for thinking of oneself in ways other than the norm predicts (Heyes, 2007, p. 119). This in turn can lead to feelings of empowerment as women experience a sense of entitlement and begin to transform their lives to create space to engage in LTPA (Currie, 2009;Deem & Gilroy, 1998;Henderson & Bialeschki, 1991).…”
Section: Ltpa and Resistancementioning
confidence: 97%
See 1 more Smart Citation
“…Physical activity is an everyday practice through which women may open up a space for "self-fashioning" and a chance for thinking of oneself in ways other than the norm predicts (Heyes, 2007, p. 119). This in turn can lead to feelings of empowerment as women experience a sense of entitlement and begin to transform their lives to create space to engage in LTPA (Currie, 2009;Deem & Gilroy, 1998;Henderson & Bialeschki, 1991).…”
Section: Ltpa and Resistancementioning
confidence: 97%
“…Postnatal depression affects up to 15% of childbearing women postpartum (Meltzer-Brody et al, 2013) and in Australia it is considered a major public health issue for mothers and their families (Australian Institute of Health and Welfare [AIHW], 2012). Women themselves have identified that LTPA is an important aspect of postnatal well-being (Currie, 2009;Daley, MacArthur, & Winter, 2007). They also, however, report difficulties continuing with formal exercise in the postnatal period for various reasons including high stress levels (Lox & Treasure, 2000), lack of energy, feeling unwell, and lack of time and space for LTPA (Doran & Davis, 2011).…”
Section: Introductionmentioning
confidence: 96%
“…The interviewed sportswomen felt society did not understand that the mother was to continue being a sportswoman and had to postpone being with her children. Similarly, both Currie's (2009) mothers and the sportswomen mothers in our study alike spoke of the guilt they experienced when they were separated from their children. They needed to have that time for themselves, but they could not help but feel guilty.…”
Section: Going Back To Sportmentioning
confidence: 84%
“…After the birth of their children, the sportswomen in this study looked for "their space" and "their moment." Currie (2009) pointed out that one of the strategies women use to feel well about being a mother is taking "a break from motherhood": a time for the woman and a break for the mother. The sportswomen from our study learned to create separate, but intertwined spheres.…”
Section: A New Identitymentioning
confidence: 98%
“…Günümüzde ise anneliğe yeni unsurlar eklenmiştir. Örneğin günümüzde annelik, planlanarak yapılan bir durumdur (Currie, 2009;Pınar, Doğan, Algıer, Kaya ve Çakmak, 2009). Çocuk bakımında modern tıp ve çocuk uzmanlarının sunduğu en yeni bilgiler kullanılmalıdır.…”
Section: Introductionunclassified